Uji Kemampuan Asap Cair dari Limbah Padat Kelapa Sawit (Elaeis guineensis jacq.) untuk Mengendalikan Hama Perusak Daun Sawi (Brassica juncea) - Priska Deyana Rima; Samharinto Soedijo; Ismed Setya Budi (www.ulm.ac.id, 2021)
Research has been carried out on the use of liquid smoke from palm oil solid waste in the form of empty bunches, shells, and fibers to determine the ability to use liquid smoke from palm oil solid waste as an insecticide in controlling pests that destroy leaves of mustard plants. This research was carried out in the Guntung Payung Payung North Loktabat vegetable plantation, North Banjarbaru. The research procedure used was a one-aspect Completely Randomized Design (CRD) experiment with 5 treatments. The treatment consisted of experiments with negative control, positive control (chemical pesticides spray volume 2ml/liter), liquid smoke of empty bunches, shells, and fibers each with a spray volume of 75ml/liter and 5 replications. The results of the research prove that the treatment of liquid smoke of palm oil solid waste does not affect the destruction of leaf destroying pests of mustard plants, but the highest damage to the control treatment and application of liquid smoke affects plant development.